Voices from Iraq: Emerging Clinical Evidence and Implications for Global Health Equity - Oluwatosin Olu-Abiodun; Redha Abdalredha; Aderinsola Faturoti; Olumide Abiodun (Babcock University Medical Journal)
This editorial emphasises the incredible potential of clinical research coming from regions affected by conflict, with a focus on Iraq's contribution to global health equity. Rather than conforming to typical narratives surrounding conflict, Iraq’s clinical research offers a fresh perspective that helps to decolonise the evidence in areas such as oncology, trauma, and maternal health. Despite facing important widespread challenges, Iraqi researchers are delivering critical and relevant insights in six key areas: (1) Gender-specific biochemical markers in rheumatoid arthritis demonstrate higher levels of uric acid and alkaline phosphatase; (2) The Bristow-Latarjet technique for treating shoulder instability achieves an impressive success rate of 75%, even under resource constraints; (3) The epidemiology of traumatic brain injuries in conflict areas reveals that blast injuries account for a staggering 39.5% of cases, whereas conservative management increases mortality risk greatly (OR=20.03); (4) Research on the hepatoprotective effects of Tribulus terrestris extract shows promise against methotrexate toxicity, offering affordable options for managing liver damage due to chemotherapy; (5) A connection between Tetraiodothyronine (T4) hormone levels and higher instances of miscarriage, preeclampsia, intrauterine growth restriction, and low birth weight; and (6) Enhanced levels of inflammatory markers (PCT, TNF-α, IL-6) combined with low zinc levels can predict disease progression, immune dysfunction, and nutritional deficiencies among lymphoma patients in resource-limited settings.